The Effect of Information Technology on the Effectiveness of Accounting Information Systems at PT Seraphim Karya Agung - Lusiana Fitrani; Novika Dwi Indriyana; Mohamad Arief Budiman; Arief Fadilah; Nursanita (Krisnadwipayana International Journal of Management Studies, 2023)
This study aims to analyze the influence of information technology on the effectiveness of accounting information systems at PT Seraphim Karya Agung. Phenomena used to test the effectiveness of accounting information systems include: data security, time, accuracy, variety of reports or output, and relevance. The inhibiting factors that exist in the implementation of accounting information systems are human resources, time and completeness of data. The solutions provided to increase the effectiveness of the accounting information system at PT Seraphim Karya Agung are: (1) improving HR soft skills, namely time discipline, by giving warnings and harsh reprimands to undisciplined employees, (2) increasing the ability of accounting information systems to overcome crash down condition of the system which can slow down the process of making financial reports, (3) related to data completeness, the accounting department of auxiliary expenditures that processes financial data that still uses a manual system to immediately transfer its use to accounting information systems by providing education and training.